1996
DOI: 10.1084/jem.183.4.1461
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation caused by lymphotoxin is lymphoid neogenesis.

Abstract: SummaryIn presenting a unifying concept for chronic inflammation and lymphoid organogenesis, we suggest that lymphotoxin's (LT, LT-ot, TNF-J3) crucial role in these processes is pivotal and similar. Chronic inflammatory lesions that developed in the kidney and pancreas at the sites of transgene expression in rat insulin promoter-LT (RIP-LT) mice resembled lymph nodes with regard to cellular composition (T cells, B cells, plasma cells, and antigen-presenting cells), delineated T and B cell areas, primary and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
297
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(312 citation statements)
references
References 47 publications
(57 reference statements)
12
297
0
3
Order By: Relevance
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%
“…These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues. LTa or LTab expression under the control of the rat insulin promoter II (RIP) induces chemokine expression and follicular lymphocytic infiltrations with mature follicular dendritic cell networks, resulting in chronic insulitis and glomerulonephritis (Picarella et al, 1992;Kratz et al, 1996;Drayton et al, 2003). Inflamed sites in RIPLTa or RIPLTab mice are vascularized with endothelia showing morphologic characteristics of high endothelial venules (Picarella et al, 1992;Cuff et al, 1999;Drayton et al, 2003).…”
Section: Lt and Inflammationmentioning
confidence: 99%
“…These chemokines induce lymphocyte immigration into the perivascular space, causing enlarged KNA, and the eventual neogenesis of a tertiary lymphoid organ, with discrete T and B cell zones (42)(43)(44)(45)(46)(47), therefore sharing many similarities with NZB thymi. The possibility that abnormal intrathymic LT signals were driving the degeneration of the medullary epithelial network was thus investigated.…”
Section: Altered Fibroblast and Endothelial Cell Populationsmentioning
confidence: 99%
“…Binding of LTα1β2 and TNF to their respective receptors, LTβR and TNFR1, induces the expression of chemokines and adhesion molecules, which directly mediate lymphocyte migration and homing [29]. The first evidence that the generation of TLS could involve the same signaling pathways that regulate lymphoid organogenesis came from studies of transgenic mice [24], in which the ectopic expression of LTα and LTβ in pancreatic islets induced the formation of in-situ TLS [30][31][32][33]. Extrapolating from this earlier experiment, stimulation of LTβR or TNFR expressed by tumor stromal cells may promote the formation of lymphoid-like structures inside the tumor tissues, which in turn may facilitate tumor destruction.…”
Section: Light Creates Lymphoid-like Tissues Inside the Tumor To Imprmentioning
confidence: 99%